The Person-Centred Care Guideline: From Principle to Practice. (December 2018) - Moody, Lesley; Nicholls, Brett; Shamji, Hannah; Bridge, Erica; Dhanju, Suman; Singh, Simron
Background: A standardized definition and approach for the delivery of person-centered care (PCC) in cancer care that is agreed upon by all key policy makers and clinicians is lacking. The PCC Guideline defines core PCC principles to outline a level of service that every person accessing cancer services in Ontario, Canada should expect to receive. This article describes the dissemination of the PCC Guideline in practice. Methods: Three strategies were utilized: (1) educational intervention via a PCC video, (2) media engagement, and (3) research/knowledge user networks. Results: As of October 2016, the PCC video has been viewed 7745 times across 92 countries. Significant mean differences pre- and post-PCC video were found for understanding of PCC principles ( P < .001) and perceived ability to bring these PCC principles to practice ( P < .001). Through content analysis, the PCC Guideline recommendations were referenced 236 times, with "Enabling Patients to Actively Participate in their Care" (n = 81), and "Essential Requirements of Care" (n = 79) being referenced most frequently. Conclusions: These strategies are an effective way to target multiple PCC stakeholders in the health-care system to increase awareness of the PCC Guideline, in order to further impart knowledge of PCC behaviors.